Uji Aktivitas Diuretik Ekstrak n-Heksana Daun Ceplukan (Physalis angulata L.) pada Tikus (Rattus norvegicus) Jantan Wistar - INDRAWATI FITRIANA; AGUNG ENDRO NUGROHO; GUNAWAN PAMUDJI WIDODO (Fakultas Farmasi Universitas Setia Budi, 2012)
Ceplukan (Physalis angulata L.) empirically have diuretic effect. This study aimed to determined the diuretic effect of n-hexane extract of ceplukan leaves on Wistar male rats. Ceplukan leaves powder were extracted by maceration with n-hexane solvent. Test animal was used 25 Wistar male rats were divided into 5 groups: group I were given CMCNa 0.5% (negative control), group II (positive control) were given furosemide dose 4.32 mg/200 g BW, group III, IV, V were given n-hexane extract suspension dose of 375, 187.5, 93.75 mg/200 g BW respectivelly. The urine volume were measured in hours-6, 12, 18 and 24. Diuretic effect is obtained by calculating the cumulative urine volume and AUC (Area Under the Curve). The data obtained were analyzed by one way ANOVA with a level of 95% significant, then test by LSD (Least Significant Difference).The results showed that n-hexane extract of ceplukan leaves had diuretic effect. The effective dose of n-hexane extract of ceplukan leaves for diuretic effect was dose 375 mg / 200 g BW.